Strategi Humas BAZNAS RI dalam Memperbaiki Citra Lembaga (Studi Kasus Pemberitaan Negatif BAZNAS di Media Online) - Mas'ud; Fajarina (Universitas Muhammadiyah Prof. DR. Hamka, 2026)
This study analyzes the communication strategies used by the Public Relations Department of BAZNAS RI to restore the institution’s image following negative online media coverage between 2022 and 2024. The controversies centered on alleged misappropriation of zakat funds in regional BAZNAS offices and BAZNAS RI’s partnership with McDonald’s Indonesia, both of which threatened public trust. Using a qualitative case study method based on Robert K. Yin’s framework, data were collected through in-depth interviews with key informants and analysis of media content and official statements. The study applies the Excellence Theory by Grunig and Hunt, Ronald D. Smith’s Strategic Public Relations Theory, and the image-building concept by Soemirat and Ardianto. BAZNAS RI’s communication strategy involved four stages: (1) Formative Research through issue mapping and media monitoring; (2) Strategic Formulation using the “3A” principles (Sharia Compliance, Regulatory Compliance, National Integrity); (3) Tactical Implementation via clarifications, leadership statements, social media, and media relations; and (4) Evaluation through media and public response monitoring. Challenges included low public literacy about BAZNAS’s structure and managing digital public opinion. The study concludes that BAZNAS RI applied a structured, transparent, and adaptive communication strategy that effectively addressed the crisis and helped maintain public trust.